Assessment the Aurora a Kinas Overexpression among Colorectal Adenocarcinoma in Iraqi Patients - Ali A. Majeed (Journal of Global Pharma Technology, 2020)
In the worldwide the colorectal carcinoma is represented the most common gastrointestinal malignancy The cancer represent one of major causes of death after cardiovascular diseases in Iraq. Aurora Kinase a (AURKA) is a member of the serine/threonine kinas family as well refers as (STK15) or (BTAK) regulates the function of centrosome, spindles, kinetochores in mitotic and chromosomal instability. AURKA overexpression is observed in various cancers including colon cancer and depended on our knowledge there is no in our country about the expression of AURKA colorectal carcinoma patients. This study included fifty five blocks embedded in paraffin was 31 (56.36%) males and 24 (43.63%) females which were obtained from colorectal adenocarcinoma patients and all samples composed of 25 (45.45%), 20 (36.36%) had moderate differentiated and (18.19%) had poorly differentiated colorectal carcinoma. The ages of patients had ranged from 20 to 80 years, with a mean of (7.44±50.6 SE).In this study, Iraqi patients showed that the protein overexpression of AURKA by immunohistochemical technique was significantly difference among these grades (p=0.0001,r=552) with high expression in well-moderate than poor differentiated while the AURKA protein overexpression was non- significant difference among different stage tumor sizes (P value =0.1746, r=0.254) as well as, the results showed there were no significant differences between AURKA protein overexpression with the gender, age and lymph-vascular and perinural invasions (P value =0.613,r=0.078), (P value 0.812, r=0.356), (p=0.711,r=0.192) respectively. Conclusion: The AURKA biomarker may be used as prognostic factor of tumor initiation in Iraqi patients with colorectal adenocarcinoma. Keywords: Iraqi patients, Colorectal Adenocarcinoma, AURKA.